GDF9 gene c.260G>A mutation and sheep litter size: a meta-analysis - Sahib, MR; AL-Jaryan, IL; Al-Thuwaini, TM (Journal of the Hellenic Veterinary Medical Society, 2024)
Growth differentiation factor 9 (GDF9) has been identified as a major gene associated with sheep litter size. The most frequent single nucleotide polymorphism (SNP) associated with GDF9 is c.260G>A, altering protein sequence. Some studies found that this SNP did not affect litter size, while others found that it had an effect. This study examined the impact of this polymorphism on litter size through a meta-analysis. An analysis was conducted on six eligible published studies to examine the effects of c.260G>A polymorphism on litter size using four different genetic models: dominant (GG + GA versus AA), recessive (GG versus GA + AA), additive (GG versus AA) and co-dominant (GG + AA versus GA). The data were analyzed according to the I-squared value using fixed-effects and random-effects models. The c.260G>A polymorphism affected litter size significantly when analyzed as recessive (SMD = -0.24, 95 % CI [-0.41, -0.08]) and co-dominant (SMD = -0.36, 95 % CI [-0.64, -0.07]). In contrast, the c.260G>A polymorphism had no effect when used with dominant (SMD = 0.35, 95 % CI [-0.26, 0.96]) and additive (SMD = 0.18, 95 % CI [-0.78, 1.15]) genetic models. A statistical sensitivity analysis of pooled SMDs revealed no differences, indicating the overall results did not result from a single study. A meta-analysis shows that sheep litter size is related to genotype GA. This study supported the concept that GDF9 is a fundamental factor that influences sheep litter size.